Impact of biofuels on U.S. retail gasoline prices: A systematic literature review - Karel Janda; Eva Michalikova; Luiz Célio Souza Rocha; Paulo Rotella Junior; Barbora Schererova; Jan Sila; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2022)
This paper summarizes the main findings of the results in the literature on the role of ethanol in reducing retail gasoline prices in the United States. We provide a comprehensive overview of the key results and methodologies used to obtain them. The paper documents the growing research interest in the assessment of the impacts of biofuels on agricultural commodity prices and overall price dynamics; presents the research trends, thematic map and the conceptual structure map; and identifes the main directions of the corn-ethanol focused biofuels literature through the analysis of predominant clusters. The last key contribution is the proposed research agenda.
Keywords: C38; Q16; Q42; 330; biofuels; corn; ethanol; gasoline; U.S. retail prices; systematic literature review